2021
DOI: 10.18502/jmr.v15i4.7743
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of Complex Structures by Persian-speaking Aphasics: The Role of Cognitive Load

Abstract: Introduction: So far, many studies have investigated the extent and nature of the grammatical deficit in aphasia. However, to the best of our knowledge, this research is the first in the Persian language to inspect the comprehension of patients with Broca’s aphasia on diverse syntactically complex structures. Materials and Methods: To scrutinize the impact of task on aphasics’ performance, four age-, education- and gender-matched Persian-speaking patients with Broca’s aphasia were compared with their hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Prefrontal dysfunction was interpreted to cause this impairment. Similarly, Azad 62 also associated metaphor‐comprehension deficit in AD patients with executive dysfunction. Papagno 64 attributed metaphor‐comprehension deficits to a failure to use contextual information to activate concepts—a pragmatic skill.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Prefrontal dysfunction was interpreted to cause this impairment. Similarly, Azad 62 also associated metaphor‐comprehension deficit in AD patients with executive dysfunction. Papagno 64 attributed metaphor‐comprehension deficits to a failure to use contextual information to activate concepts—a pragmatic skill.…”
Section: Discussionmentioning
confidence: 87%
“…In their seminal work, Winner and Gardner 59 found that AD patients were impaired in the metaphor comprehension task. Since then, several studies 20,42,43,45,47,54,[60][61][62][63][64] have investigated metaphorcomprehension deficits in patients with dementia. Most of these studies, except some recent ones 44,45,47,60,63 focused only on people with AD.…”
Section: Metaphormentioning
confidence: 99%